An Obstacle to Decolonising Europe: White Nationalism and Its Co-option of Serbian Propaganda. Issue 2 (1st September 2021) - Kiper, Jordan
Abstract: While the central aim of decolonisation is undoing colonial legacies, a major obstacle is white nationalism. A new wave of transnational anti-globalist, Islamophobic, and white-grievance tropes have hybridised with local political ideologies of right-wing politics and authoritarian populists in Europe and the United States. Here, I review the cultural characteristics of this new wave of white nationalism by focusing on its co-option of Serbian nationalist propaganda from the Yugoslav Wars and shared receptivity to narratives among far-right political groups in former colonial powers. The portrait that emerges is one of cross-cultural variations on a common theme: maintaining white supremacy and actively countering ideological challenges to it. Critically, the new wave of white nationalism expands our anthropological understanding of white supremacy but also highlights the significance of white nationalism in obstructing justice initiatives that address the race crimes of colonialism. Less consensus has been reached, however, on how to counter white nationalist networks and transnational extremist propaganda. In addition to highlighting ways to counter white nationalist propaganda, I argue that decolonising Europe and achieving its envisioned relations of sociative peace will not be fully realised unless more is done to minimise the influence of white nationalism.